Fluidity Influencing Factors Analysis and Ratio Optimization of New Sealing Materials Based on Response Surface Method. (3rd March 2021) - Guo, Xin; Xue, Sheng; Li, Yaobin; Zheng, Chunshan; Yang, Gege
Abstract : The borehole sealing material is one of the key factors affecting the gas drainage effect of a borehole. This paper takes the compressive strength, fluidity, expansion rate, and setting time of the sealing material as the main research indicators and explores the influence of each key influencing factor on the performance of the high-fluid sealing material through the single factor experiment method. Using the Design-Expert 8.0.5 Trial software designed orthogonal experiments and establishing a quadratic model between liquidity and each test factor, which showed the impact of each key factor on the fluidity. Finally, by adjusting the amount of admixtures, the optimal ratio of high-fluidity borehole sealing materials was obtained. The results showed that the key factors had the following order of significance: water – cement   reducing   agent > water – cement   ratio > retarder > expansion   agent . With the water-cement ratio and the amount of water reducing agent increase, the fluidity of the material will increase; and with the increase of the retarder and expansion agent, the fluidity will decrease. In actual use, the fluidity is the main factor, but the expansion rate, compressive strength, and setting time are also considered. The optimal percentages were found for the high-fluidity borehole sealing material: a water-cement ratio of 1, along with 0.03% retarder, 0.5% water reducer, and 8% expansion agent. These research results could provide a reference for improving the performance of gas drainage borehole sealing materials and enhancing the effect of gas drainage.